Abdominal perforator exchange flap (APEX): A classification of pedicle rearrangements. Issue 7 (13th August 2021) - Zoccali, Giovanni; Farhadi, Jian
Abstract: Introduction: Abdominal‐based reconstruction is the most commonly performed method for breast reconstruction after mastectomy using the patient's own tissues. DIEP flap has allowed to reduce the donor site morbidity but the incidence of bulging or hernia remains still high, especially when flap is based on multiple perforators. Abdominal Perforator Exchange flap (APEX) represents a further step forward in preserving the abdominal wall structures by disassembling the pedicle components and their reconstitution at the end of the dissection. In this study, we explore the possible anatomical configurations of perforators exchange for APEX, providing a simple classification of perforators reconstitution patterns and the possible clinical implications. Materials and methods: A retrospective study was conducted on patients who received APEX flap for abdominal based breast reconstruction. Preoperative CT scans and procedure descriptions were analyzed to identify the vascular patterns during flap harvesting and the pedicle reconstitution sites. The onset of abdominal wall and flap related complications were investigated. Results: APEX flap was performed on 51 women and four vascular patterns were identified. We identified the Type A pattern in 36 cases (70.6%), the Type B pattern in 8 (15.7%), and the Type C pattern in 5 (9.8%). We performed an extra‐anatomical reanastomosis (Type D) in only two case (3.9%) ( p = .09). We recorded anastomotic problems in five pedicles' reconstitution and the odds ratio showed a possible correlation between the localization of pedicle division and the anastomosis problems ( p > .05). No total or partial flap loss was recorded during this study. Marginal fat necrosis was clinically observed in three cases, which had very large flaps. No bulging or hernia was recorded. Conclusion: Our perforators exchange classification for abdominal‐based flap helps clinician in planning the surgery and also in describing the procedure easily allowing a more efficient communication. This classification could be used to approach perforator flaps with multiple vessels at other anatomical locations as well.